Anticancer Effects of Sinapic Acid on Human Colon Cancer Cell Lines HT-29 and SW480 - Nalini, Namasivayam (International Journal of Pharmaceutical & Biological Archive, 2015)
Anticancer Effects of Sinapic Acid on Human Colon Cancer Cell Lines HT-29 and SW480